Ethnomathematical Exploration of Tembe Nggoli Mbojo Local Culture - Fitriani, Ainun; Irawan, Ady; Munandar, M. Imam; Akbar, Haiful Kamal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Mathematics is a field of study that emphasizes logical and systematic reasoning. From a cultural perspective, mathematics is closely related to various community activities, which can be examined through the ethnomathematics approach. This study aims to explore ethnomathematical elements embedded in Tembe Nggoli Mbojo, a traditional woven fabric of the Bima community in West Nusa Tenggara. The research employed a qualitative method using observation, documentation, and interviews with local weavers and cultural figures. The findings reveal that the motifs of Tembe Nggoli Mbojo contain mathematical concepts such as geometric transformations (including two-dimensional shapes such as squares, rectangles, triangles, parallelograms, and rhombuses), patterns, and symmetries. These results indicate that Tembe Nggoli Mbojo not only possesses aesthetic values but also contributes to contextual mathematics learning that is culturally relevant, while simultaneously supporting cultural preservation and reinforcing national identity.